Aplikasi Penentuan Peringkat Kabupaten Terbaik Tingkat Provinsi Sumatera Utara Menggunakan Metode WASPAS - Nasrul Hidayat Harahap; Mesran Mesran; Murdani Murdani (STMIK Budi Darma, 2021)
Determining the best ranking of districts in the Province of North Sumatra is done by determining the existing criteria, so the North Sumatra provincial government will easily determine which districts will be ranked as the best districts. selection is done by looking at the data that is in the North Sumatra provincial government and how the district has performed for the previous year. The problem faced by the selection team is how to determine the best districts from a number of alternatives that have advantages and disadvantages of each district so that they are not well targeted in providing the best assessment to be analyzed. This system is a Decision Support System (SPK) which was built using the WASPAS method and designed using Microsoft Visual Studio 2008 and using a Microsoft Access database. Data processing will be carried out by the Selection Team from North Sumatra provincial government by entering data or criteria for the district. then the system will perform calculations according to the WASPAS principle which will eventually produce a ranking of the best districts in the province of North Sumatra.